Comparative Evaluation of Shear Bond Strength of Newer Generation Bonding Agents: An in-vitro study (Orthodontic Journal of Nepal, 2025)
Introduction: This in-vitro study aimed to compare the shear bond strength (SBS) of stainless steel (SS) orthodontic brackets bondedwith three different generations of bonding agents.Materials and Methods: Ninety extracted maxillary 1st premolars were bonded with stainless steel brackets using three different generations of bonding agents: a) GROUP 1: Transbond XT (fifth generation, light cure adhesive,3M Unitek, USA), b) GROUP 2: Shofu bond II (sixth generation, self-etching primer), c) GROUP 3: Adper single bond 2 (seventh generation, 3M ESPE, USA) according to their manufacturer’s instructions & tested for shear bond strength with an Instron universal testing machine & results were obtained.Results: The SBS values for group 1 was 12.3MPa, group 2 was 11.9MPa, and group 3 was 13.2MPa. The ANOVA and Tuckey’s post hoc analysis revealed statistically significant differences among groups 1 & group 3 (p ≤ 0.05).Conclusion: All the bonding agents yielded adequate SBS values (within a range of 8-14 MPa), among which the seventh generation showed the highest shear bond strength values.